Pembinaan Karakter Kristiani Dalam Membentuk Potensi Diri Bagi Peserta Didik Di SMP Clarissa Batam - Sabar Manahan Hutagalung; Putri Jelita Daeli; Laura Purba; Nencis Laylele; Fransiska Mitalia; Novi Yanti Palentina Pakpahan; Putri Suheri Manurung; Novita Sari Dewi Butar-Butar; Janet Eliana Manurung; Griya Immanuel (Universitas Katolik Widya Karya Malang, 2023)
Character is a trait possessed by an individual that is embedded in the soul and body, which is implemented through actions. In this day and age Christian character education is very minimal in Christian students, this can happen due to a lack of provision from parents regarding Christian character. If this continues to happen and is not resolved, it will become one of the obstacles in growing the nation's successors who have the potential to advance the nation. Therefore, the school has a very big role in teaching this to students, so that students have the correct Christian character, especially in dealing with the social life of children in the present. In solving this problem, the authors use the stages which include: Observation, implementation of PKM, and evaluation. The result of this PKM activity is to increase students' awareness of themselves not to continue to be in bad conditions so that the potential they have can be developed properly